2018
DOI: 10.1097/aog.0000000000002562
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Detoxification During Pregnancy

Abstract: OBJECTIVE To systematically review maternal and neonatal outcomes associated with opioid detoxification during pregnancy. DATA SOURCES PubMed, PsycINFO, EMBASE, Cochrane, and ClinicalTrials.gov databases were searched from January 1, 1966, to September 1, 2016. METHODS OF STUDY SELECTION English-language studies that reported outcomes associated with opioid detoxification among pregnant women with opioid use disorder were included. Nonoriginal research articles (case reports, editorials, reviews) and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 39 publications
0
67
0
Order By: Relevance
“…As this study was in preparation, Terplan et al published a systematic review evaluating both maternal and neonatal outcomes with opioid drug detoxification in pregnancy. 56 Their review included two studies that ours did not. One was a 1975 publication that included patients who were managed prior to 1980.…”
Section: Discussionmentioning
confidence: 99%
“…As this study was in preparation, Terplan et al published a systematic review evaluating both maternal and neonatal outcomes with opioid drug detoxification in pregnancy. 56 Their review included two studies that ours did not. One was a 1975 publication that included patients who were managed prior to 1980.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest systematic review to date that included 1126 pregnant women with OUD who underwent opioid detoxification, rates of successful detoxification (9e100%) and illicit drug use (0e100%) were widely variable. 101 The high rates of successful detoxification (as high as 100% in some studies) as judged by no evidence of opioid use recurrence on urine drug screen at the time of delivery occurred in studies in which women were in inpatient residential treatment programs, including involuntary institutionalization. The rates of relapse were dependent on the inclusion or exclusion of women who were lost to follow-up.…”
Section: Medication-assisted Withdrawalmentioning
confidence: 99%
“…Similarly, given the significant bias and poor-to-fair quality of previous studies, at present any risks for pregnancy, fetal, and newborn complications that are associated with opioid withdrawal during pregnancy remain both unidentified and unquantified. 101 The elements of optimal care for pregnant women who choose medication-assisted withdrawal have not been well described, and future research in this area is needed before it can be recommended as a standard option.…”
Section: Smfm Special Reportmentioning
confidence: 99%
“…Current recommendations for treating women with OUD during pregnancy emphasize behavioral therapy and access to pharmacotherapy, including methadone, buprenorphine (Subutex), or buprenorphine‐naloxone (Suboxone) . Two recent systematic reviews have found that detoxification, defined as assisted or unassisted withdrawal from opioids without initiation of pharmacotherapy, increases the risk of relapse . However, despite current recommendations, the majority of pregnant women with OUD do not receive pharmacotherapy during pregnancy .…”
Section: Introductionmentioning
confidence: 99%